1992
DOI: 10.1007/bf01250964
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-aminobutyrate aminotransferase activity in brains of schizophrenic patients

Abstract: The activity of gamma-aminobutyrate aminotransferase (GABA-T) was estimated in twelve regions of brains from 22 control subjects and 6 cases with schizophrenia. In the controls, no significant correlation was found between the enzyme activity and age or postmortem interval (PMI) in any of the brain regions studied. In experiments on rat brains, the enzyme activity decreased about 20% during the first 2 hours of storage at room temperature and at 4 degrees C but remained steady thereafter. A similar initial dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
2
3
1
Order By: Relevance
“…Measurements of five glutamate-associated (glutamate dehydrogenase, glutamine synthetase, AST, ALT, and α-ke-toglutarate dehydrogenase) and two GABA-associated enzymes (GABA-transaminase and succinic semialdehyde dehydrogenase) in the dorsolateral prefrontal cortex showed no significant activity differences between the schizophrenic and comparison groups. Similar results (regarding GABA-transaminase) have been reported by Sherif et al (42). Thus, the abnormalities noted in glutamic acid decarboxylase and phosphate-activated glutaminase activity are not attributable to a global disruption of metabolic pathways, subject selection bias, or other uncontrolled experimental artifacts.…”
Section: Unchanged Metabolizing Enzymessupporting
confidence: 88%
See 1 more Smart Citation
“…Measurements of five glutamate-associated (glutamate dehydrogenase, glutamine synthetase, AST, ALT, and α-ke-toglutarate dehydrogenase) and two GABA-associated enzymes (GABA-transaminase and succinic semialdehyde dehydrogenase) in the dorsolateral prefrontal cortex showed no significant activity differences between the schizophrenic and comparison groups. Similar results (regarding GABA-transaminase) have been reported by Sherif et al (42). Thus, the abnormalities noted in glutamic acid decarboxylase and phosphate-activated glutaminase activity are not attributable to a global disruption of metabolic pathways, subject selection bias, or other uncontrolled experimental artifacts.…”
Section: Unchanged Metabolizing Enzymessupporting
confidence: 88%
“…The activity of glutamic acid decarboxylase was greater by nearly twofold in the dorsolateral prefrontal cortex of schizophrenic subjects and correlated significantly and positively with the activity of phosphate-activated glutaminase-especially in the schizophrenia group-making it unlikely that disease-independent influences on phosphate-activated glutaminase and glutamic acid decarboxylase activities would lead to disease-specific correlations between the activities of the two enzymes. Similarly, since the N-acetylaspartate, N-acetylaspartyl-glutamate, and GABA-transaminase data reproduced the findings of others (3,42), it is unlikely that the higher activity of glutamic acid decarboxylase was artifactual. There are two isoforms of glutamic acid decarboxylase (glutamic acid decarboxylase 65 and glutamic acid decarboxylase 67 ), which are encoded by different genes (47).…”
Section: Higher Activity Levelssupporting
confidence: 76%
“…No significant effect of sex, psychotic state, length of illness or medication treatment was noted in the study by White et al (1980) ; Reveley et al (1980) reported no correlation between age or sex and GABA-transaminase levels. Sherif et al (1992) measured GABA-transaminase in brain homogenates from various regions including hippocampus, amygdala, cingulate and frontal gyrus and found no significant difference between controls and undifferentiated schizophrenics. Thus, there is no evidence of altered catabolism of GABA in schizophrenia.…”
Section: Gaba-transaminasementioning
confidence: 98%
“…GABA-T activity was determined by following the method of Sherif et al [16]. 3.02 mL final assay reaction mixture contained 86 mM potassium pyrophosphate, 3.3 mM 2-mercaptoethanol, 1.2 mM β -nicotinamide adenine dinucleotide phosphate, 5 mM a-ketoglutarate, 6.0 mM γ -amino-n-butyric acid, 0.50 mM potassium phosphate, and 0.17% (v/v) glycerol with 0.02 mL of enzyme source.…”
Section: Methodsmentioning
confidence: 99%